Numerical study of Rayleigh-Bénard natural-convection heat-transfer characteristics of water-based Au nanofluids - Ternik, Primož (Materiali in tehnologije, 2013)
The present work deals with the natural convection in a square cavity filled with a water-based Au nanofluid. The cavity is heated from the lower and cooled from the adjacent wall, while the other two walls are adiabatic. Theg overning differential equations have been solved with the standard finite volume method and the hydrodynamic and thermal fields have been coupled using the Boussinesq approximation. The main objective of this study is to investigate the influence of the nanoparticlesć volume fraction on the heat-transfer characteristics of Au nanofluids at a given base-fluid (i.e., water) Rayleigh number Rabf. Accurate results are presented over a wide range of the base-fluid Rayleigh numbers (102 L Rabf L 105) and the volume fraction of Au nanoparticles (0 % L j L 10 %). It is shown that adding nanoparticles to the base fluid delays the onset of convection. Contrary to what is argued by many authors, we show, with numerical simulations, that the use of nanofluids can reduce the heat transfer instead of increasing it.
Keywords: nanotekočine; konvekcija; prenos toplote; numerično modeliranje